Effect of tongue‐strengthening exercises on tongue strength and swallowing‐related parameters in chronic radiation‐associated dysphagia. Issue 9 (30th April 2020) - Van den Steen, Leen; Baudelet, Margot; Tomassen, Peter; Bonte, Katrien; De Bodt, Marc; Van Nuffelen, Gwen
Abstract: Background: Radiation‐associated dysphagia (RAD) is highly prevalent in head and neck cancer (HNC) patients, with insufficient tongue strength (TS) as a characteristic of this disabling complication. The effects of tongue‐strengthening exercises (TSE) on TS, swallowing, and quality of life (QoL) have not been studied in this population. Methods: A prospective phase 2 study using an 8 weeks during TSE protocol was carried out in 15 patients with chronic RAD. Outcome parameters were maximal isometric pressure (MIP), TS during swallowing (Pswal), swallowing function, and QoL. All parameters were evaluated at baseline, after 4 and 8 weeks of training, and 4 weeks after the last training session. Results: MIP increased significantly, without detraining effects. Pswal did not increase significantly, but relevant effect sizes were measured. Swallowing function ameliorated, but did not result in increased functional oral intake, self‐reported outcome or QoL. Conclusion: TSE in patients with RAD results in increased strength and swallowing function.